Statlig hallickverksamhet? - Försäljning av sexuella tjänster som skattepliktig inkomst - Burman,Sofia (2024)
Since 1999, the purchase of sexual services is illegal in Sweden. The criminalization was a result of several government investigations and a part of the women's integrity reform. It was motivated mainly by two interests: on the one hand the protection of the weaker party, who is often exploited by the buyer, and on the other hand the general public were mentioned in the legislative history. In the evaluation investigation ten years later, it was noted that there had been a certain shift in the protection interest, where focus had been moved toward the individual's personal and sexual integrity. In November 2023, the report "Ut ur utsatthet" was published, describing a shift in the view of those who sell sexual services. The Supreme Administrative Court addressed the issue of taxation of income related to sexual services in a ruling from 1982. It concerned a woman who was required to pay tax in the income category of business activities on income of this sort. Lower courts have referred to this ruling even after the prohibition on the purchase of sexual services was introduced. The courts have argued that criminalization does not affect the tax assessment. The issue has received significant attention over the past year and has been questioned by politicians and the organization Talita, among others. The Swedish Tax Agency has responded to the criticism by referring to their obligation to adhere to the law. Tax law is based on its fiscal purpose and the requirement for legal certainty. One of the most important taxes in Sweden is the income tax, and individuals' earned incomes are taxed in accordance with a legislated procedure based on personal declarations. In the essay’s analysis, arguments for and against tax exemption for prostitutes are presented. Various aspects are raised regarding the protection interest of the individual in relation to tax law principles. There are certain problems with comparing two distinct regulatory systems, but it appears necessary for the purpose of this essay. The conclusion finds that there are clear conflicts of interests between criminal law and tax law and suggests encouraging a potential investigation into the tax liability of income from prostitution.
Keywords: rättsvetenskap; skatterätt; straffrätt; rättshistoria; prostitution; sexuella tjänster; förvaltningsrätt; inkomstskatt; sexköpslagen; skatteverket